Urticaria and mimickers of urticaria - Fok, Jie Shen; Katelaris, Constance H. (Frontiers in Allergy, 2023)
Urticaria is a common skin condition encountered across various specialties in medicine, especially in dermatology and allergy/immunology practice. It has a heterogeneous presentation hence it is unsurprising that many skin conditions may be confused with urticaria. Urticaria may present as acute or chronic urticaria, the latter can be further categorised into chronic spontaneous and chronic inducible. In this article, we explore, explain, and summarise various skin lesions that are considered mimickers of urticaria, to promote understanding of each of the conditions highlighted, improve recognition, and reduce misdiagnosis.